PERLINDUNGAN HUKUM BAGI BANK TERHADAP PEMBELIAN RUMAH INDENT SECARA KREDIT PEMILIKAN RUMAH (KPR) MELALUI DEVELOPER PERUMAHAN (STUDI PADA PT. BANK NEGARA INDONESIA (PERSERO) TBK. LOAN CENTRE MEDAN) - ISRA KUSNADI (PREMISE LAW JURNAL, 2015)
KPR (Home Ownership Credit) is a banking product for financing the purchase of ready stock or indent houses. Buying an indent house causes the Bank to be in a weak position since the contract is signed before the house has not been built yet. The research used judicial normative and descriptive analytic method. The data were gathered by using secondary data from library research and primary data from interviews. The regulation on legal correlation between the Bank and a developer in buying an indent house by KPR is stipulated in the Circular Letter of Bank Indonesia No. 15/40/DK/DKMP on September 24, 2013 on the Implementation of Risk Management for the Bank which Gives Credit or Finances Property Ownership. The problem is when a developer is default in building the houses and a debtor is default in paying for the installment. Legal protection for the Bank is by assessing developers and debtors, controlling the construction of the houses and doing buyback guarantee. Keywords: Legal Protection, Indent Housing, KPR (Home Ownership Credit)